Transformation of an Agulhas eddy near the continental slope - S. Baker-Yeboah; G. R. Flierl; G. G. Sutyrin; Y. Zhang (Ocean Science, 2010)
The transformation of Agulhas eddies near the continental slope of southern Africa and their subsequent self-propagation are analyzed in both observational data and numerical simulations. Self-propagation results from a net dipole moment of a generalized heton structure consisting of a surface-intensified anticyclonic eddy and deep cyclonic pattern. Such Agulhas vortical structures can form near the retroflection region and further north along the western coast of southern Africa. We analyze nonlinear topographic wave generation, vortex deformations, and filament production as an important part in water mass exchange. Self-propagating structures provide a conduit for exchange between the deep ocean and shelf regions in the Benguela upwelling system.

Formulation of an ocean model for global climate simulations - S. M. Griffies; A. Gnanadesikan; K. W. Dixon; J. P. Dunne; R. Gerdes; M. J. Harrison; A. Rosati; J. L. Russell; B. L. Samuels; M. J. Spelman; M. Winton; R. Zhang (Ocean Science, 2005)
This paper summarizes the formulation of the ocean component to the Geophysical Fluid Dynamics Laboratory's (GFDL) climate model used for the 4th IPCC Assessment (AR4) of global climate change. In particular, it reviews the numerical schemes and physical parameterizations that make up an ocean climate model and how these schemes are pieced together for use in a state-of-the-art climate model. Features of the model described here include the following: (1) tripolar grid to resolve the Arctic Ocean without polar filtering, (2) partial bottom step representation of topography to better represent topographically influenced advective and wave processes, (3) more accurate equation of state, (4) three-dimensional flux limited tracer advection to reduce overshoots and undershoots, (5) incorporation of regional climatological variability in shortwave penetration, (6) neutral physics parameterization for representation of the pathways of tracer transport, (7) staggered time stepping for tracer conservation and numerical efficiency, (8) anisotropic horizontal viscosities for representation of equatorial currents, (9) parameterization of exchange with marginal seas, (10) incorporation of a free surface that accomodates a dynamic ice model and wave propagation, (11) transport of water across the ocean free surface to eliminate unphysical ``virtual tracer flux" methods, (12) parameterization of tidal mixing on continental shelves. We also present preliminary analyses of two particularly important sensitivities isolated during the development process, namely the details of how parameterized subgridscale eddies transport momentum and tracers.